ANALISIS PELAKSANAAN PEMBELAJARAN BIOLOGI JARAK JAUH DI MASA PANDEMI COVID-19 DI SMAN 3 BANTAN (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This study aims to analyze the implementation of Distance Biology Learning during the Covid-19 Pandemic at SMAN 3 Bantan. Descriptive research conducted in SMAN 3 Bantan the time used to carry out this research is August-October 2021. Sampling using total sampling techniques, The research sample is all X-class students and class XI students of SMAN 3 Bantan for the 2020/2021 school year. The number of class X students amounted to 26 and class XI students amounted to 18 students with a total of 44 students. Research instruments used in the form of interviews and questionnaires. Before use the questionnaire has gone through the validity and reliability test stage. The results showed that the average percentage of distance biology learning implementation during the Covid-19 pandemic in SMAN 3 Bantan with material indicators to be taught was 75.75% with good category. on the learning profile indicator, student conditions and needs are 76.90% with good category, while in the indicator of design and implementation of distance learning is 72.02% with good category. The implementation of distance biology learning during the Covid-19 pandemic at SMAN 3 Bantan shows that it has been going well.Key Words: Distance Learning, Pandemic, Biology Learning